Zebrafish High‐Throughput Screening to Study the Impact of Dissolvable Metal Oxide Nanoparticles on the Hatching Enzyme, ZHE1. Issue 9 (23rd November 2012) - Lin, Sijie; Zhao, Yan; Ji, Zhaoxia; Ear, Jason; Chang, Chong Hyun; Zhang, Haiyuan; Low‐Kam, Cecile; Yamada, Kristin; Meng, Huan; Wang, Xiang; Liu, Rong; Pokhrel, Suman; et al.
Abstract The zebrafish is emerging as a model organism for the safety assessment and hazard ranking of engineered nanomaterials. In this Communication, the implementation of a roboticized high‐throughput screening (HTS) platform with automated image analysis is demonstrated to assess the impact of dissolvable oxide nanoparticles on embryo hatching. It is further demonstrated that this hatching interference is mechanistically linked to an effect on the metalloprotease, ZHE 1, which is responsible for degradation of the chorionic membrane. The data indicate that 4 of 24 metal oxide nanoparticles (CuO, ZnO, Cr2O3, and NiO) could interfere with embryo hatching by a chelator‐sensitive mechanism that involves ligation of critical histidines in the ZHE1 center by the shed metal ions. A recombinant ZHE1 enzymatic assay is established to demonstrate that the dialysates from the same materials responsible for hatching interference also inhibit ZHE1 activity in a dose‐dependent fashion. A peptide‐based BLAST search identifies several additional aquatic species that express enzymes with homologous histidine‐based catalytic centers, suggesting that the ZHE1 mechanistic paradigm could be used to predict the toxicity of a large number of oxide nanoparticles that pose a hazard to aquatic species.